THE SEMIOTIC COMPONENT OF LACUNS AND THEIR BASIC TYPES IN THE LANGUAGE: THEORETICAL SUBSTANTIATION - Shaker, Inas Tarek (Al-Adab Journal, 2020)
The article attempts to provide the theoretical fundamentals for the semiotic component of lacunae in a language. The definitions of the following notions have been represented: 1) lacunarity as a complex phenomenon that works in the modes of language, speech and speech behaviour; 2) lacuna as a gap, an empty space, which lacks something, which may be characteristic of a written work. The author of the article considers the main classes of lacunae, among which are: 1) generic lacunae, which reflect the absence of a common name for a class of objects; 2) species lacunae are the absence of specific names, names of individual types of objects or phenomena; 3) intralingual lacunae are found within the paradigms of one language; 4) interlanguage lacunae are revealed when comparing different languages: if one of them does not have the lexical equivalent of any unit of another language, then it is possible to speak about the existence of a lacuna in it; 5) grammatical lacunae are the result of phonetic, prosodic, morphological weakening or erosion of elements, which often become the cause of the approval of a new lexical, phonetic or grammatical form; 6) phonosemantic lacunae arise in line with the general linguistic tendency to phonetic harmoniousness, they are withdrawn from rare use.